EFFECT OF A DENSITY DISCONTINUITY ON THE CONVECTIVE STABILITY OF THE MANTLE - Birger B.I. (My University, 1988)
We analyze the convective stability of a system consisting of two infinite horizontal layers separated by a contact boundary which in the case of hydrostatic equilibrium is planar and is located at a fixed depth. The layers differ only in density, which is assumed to be higher in the lower layer than in the upper layer. The temperatures of the outer boundaries are fixed, with the temperature of the lower boundary being higher than that of the upper. The results obtained from perturbation theory may be used as a basis for numerical analysis of the problem.